Wymaganie obecności na zajęciach w czasie choroby jako przykład ukrytego programu studiowania medycyny - Kaczmarek, Emilia; Makowska, Marta (Annales. Etyka w Życiu Gospodarczym, 2020)
Considering medical students’ experiences gives insights into aspects of their education and socialization to the medical profession that are not visible from official curricula. This article presents the results of a multi-thread focus group study involving medical students studying at three Polish medical universities. The aims of the article are: 1) to describe the surveyed students’ experiences regarding difficulties associated with missing classes and justifying their absence, and; 2) to confront these experiences with their universities’ policies and professional ethics demands that require the development of pro-health attitudes. The practices described by the respondents are considered to constitute an example of a “hidden curriculum”, i.e. the shaping of students’ attitudes not through officially taught content, but, rather, through widespread customs in a given institution. The conclusion is that the medical students’ experiences are inconsistent with Polish law and the regulations of their universities. The described practices also seem to be inconsistent with Article 71 of the Polish Code of Medical Ethics, which prohibits doctors from promoting anti-health attitudes.